Outcomes after therapeutic SBE-ERCP for choledochojejunal/hepaticojejunal anastomotic stenosis after bile duct injury - Shu, Yijun; Koo, Pak-Lam; Weng, Hao; Pan, Li-Jia; Weng, Ming-Zhe; Yang, Ziyi; Zhao, Ming-Ning; Zhang, Wen-Jie; Gu, Jun; Gong, Wei; Mei, Jia-Wei; Liu, Yingbin; et al. (Frontiers in Surgery, 2025)
BackgroundCholedochojejunal/hepaticojejunal anastomotic stenosis (CJS/HJS) is significant clinical problem associated with decreased survival postsurgery. Endoscopic retrograde cholangiopancreatography (ERCP) using single-balloon enteroscopy (SBE) is the first-line management strategy for such conditions. However, studies on the risk factors and outcomes of endoscopic management strategies for CJS/HJS in biliary duct injury (BDI) are extremely limited.MethodsWe conducted a retrospective review of patients with symptomatic BDI who underwent choledochojejunal/hepaticojejunal Roux-en-Y anastomosis between April 2009 and April 2019. The primary endpoint was CJS/HJS recurrence. The secondary endpoint was early (i.e., emergent or unplanned) repeat SBE-ERCP (ER-SBE-ERCP). We also evaluated the details of initial therapy, complications, and treatment for CJS or HJS recurrence.ResultsFrom April 2009 to April 2019, 112 patients were treated, and 45 (40.2%) BDI patients developed CJS/HJS. Operation type (P < 0.001), salvage surgery timing (P = 0.005), hepatic artery injury (P = 0.001), bile leakage after surgery (P < 0.001) and recurrent cholangitis (P < 0.001) were significantly associated with anastomotic stenosis. The overall CJS/HJS recurrence rate was 27.9% (12/43). Of all the patients, 79.1% (34/43) underwent balloon dilation at the anastomotic stenosis site; stent placement was performed in 33 of 43 patients (76.8%). The complication rate was 7% (3/43).Initial balloon dilation (P = 0.024) was associated with the proportion of patients requiring ER-SBE-ERCP. Predictors of CJS/HJS recurrence on bivariate analysis included initial balloon dilation (P < 0.001) and ER-SBE-ERCP (P < 0.001). On multivariate analysis, ER-SBE-ERCP was significantly associated with CJS/HJS recurrence, likely reflecting the presence of more severe lesions or higher baseline risks for recurrence, rather than being a direct cause of recurrence.ConclusionsInitial balloon dilation is associated with a decreased risk of CJS/HJS recurrence. ER-SBE-ERCP is more commonly performed in patients with severe anastomotic lesions or higher baseline risks for recurrence, which may contribute to the higher observed recurrence rates of CJS/HJS in this group.